AUGMENTED REALITY- BASED DOJO SAFETY HANDBOOK - Ismara, Ketut Ima; Kamil, Hasan Rahmat; Prianto, Eko; Damarwan, Eko Swi (Universitas Dharma Wacana, 2022)
Study this aim to (1) Produce learning media in the form of textbooks entitled Augmented Reality-Based Safety Dojo Guidebook for Vocational subjects, (2) Knowing appropriateness from learning media in the form of textbooks , (3) knowing rating and feedback student related textbooks in the form of Book Guidelines Safety Dojo AR based .Type Study this including in Research and Development ( RnD ) research with use ADDIE approach which includes Analysis, Design, Development, Implementation, Evaluation stages .Study this conducted at SMK Hamong Putra Pakem . Then validation from product book this done by expert respective materials and media experts each totaling 2 people. Material expert involving 1 person from a vocational school teacher and 1 lecturer major electro, while from media expert involves 2 lecturers from major UNY electronics . For testing product done by students Class X and XI Department of Electrical Power Installation Engineering at SMK Hamong Putra Pakem as many as 40 students . This research instrument is in the form of a printed questionnaire which is then distributed to respondents, and through direct interviews. Whereas for the data obtained in the form of qualitative and quantitative data which are then analyzed with analysis validity reliability .Study this produce : (1) Learning Media in the form of a textbook with the title